MODERN TOTEMS AND TRIBALISM: THE WORSHIPING OF BRANDS IN ASIA - Luca Scaini; Daniela Navarra (European Scientific Journal, ESJ, 2015)
The present paper is going to explore what is nowadays a brand and a logo in the far Asian cultural environment, approaching it both socially and economically, from a socio-psychological and commercial point of view. Moving throughout some very physioeconomical angle and narrowing on consumer’s behavior toward the brands’ values, it proofs how tribes pop up around life styles and logos (Hitmann & Ward 2007; Anderson 1990). The motivation of present paper is the huge importance related to brand and modern (urban) tribalism, especially in the far Asiatic environment, observing the phenomena both like social (Bucci, Cova, Kozinets 2007; Cova 2003) and economical (Badot, Bucci, Cova 2003; Temporal 2012). The paper is analyzing Brand like a catalyzer of different perceptions of syncretized together (Hitman & Ward 2007; Scaini 2012; Fabris 2003, 2008; Conley 2009). To prove the actual importance of behavior of consumer in the Asiatic environments, the paper offers some qualitative result based on a solid limited quantitative research. Offering a theoretical approach (proofed by evidences gathered) about the activities of brands on eastern Asian markets, it states that now brands behave like totemic relics of deity (Conley 2009; Hebdige 198110), that is really the center of the new Asiatic worship replacing disrupted traditional values and replacing with new iconic symbols of social membership (Diamond 2005; Anderson 1990, Mishima 200815).